Small-sward testing of Stylosanthes in Northern Australia: Preliminary considerations - Burt, R.L.; Edye, L.A.; Williams, W.T.; Gillard, P.; Grof, Bela; Page, M.; Shaw, N.H.; Williams, R.J.; Wilson, G.P.M. (Commonwealth Scientific and Industrial Research Organisation, 1974)
An experiment is described in which 27 accessions of Stylosanthes, comprising some seven species, were grown for 3 years in small swards at eight different sites covering a wide range of environments. The accessions used were selected on the basis of previous studies, so as to represent a wide range of species and species forms. Numerical data was used to delineate those species, or species forms, likely to be of agronomic value in the various areas. The implications of the methods used and the results obtained are discussed in relation to plant introduction and plant evaluation techniques.